The Current Updates of the Progresses and the Challenges of Recognition of Customary Forests in Indonesia - Rikardo Simarmata (Jurnal Ilmu Kehutanan, 2024)
Around 30 million Indonesians are forest-dependent, comprising a large portion of customary communities. For generations, customary communities managed forests using customary arrangements as the normative system. However, the state legal framework required the communities to obtain legal recognition to exercise these traditional forest rights. Over the last seven years, the state has formalized hundreds of thousands of hectares of customary forest, which was unprecedented. Some suggested that the number needed to be increased and far less than the potential customary forest areas. Therefore, this research aimed to examine the primary cause and the subsequent impacts on the low number of recognized customary forests. Relevant data were obtained for analysis from documents and direct interviews. The result showed that customary tenure on forest resources coexisted with the state arrangements. The state recognized those customary arrangements through formalization. However, the ideological and political perception and the state's interests regarding customary communities have brought obstacles to that sound policy regarding recognition. This perception and interest further raised three issues regarding the current legal framework and its implementation: complex regulation, delayed processing time, and ambiguous standards.